Essentials of law and ethics for pharmacy technicians - Strandberg, Kenneth M. (CRC Press pharmacy education series ;, 2012)
"As the practice of modern medicine becomes more and more pharmacology dependent, the role of pharmacy technicians is becoming more complex. This is true in terms of the medications they are required to deliver, as well as the legal responsibilities and ethical considerations that come with administering those medicines. Essentials of Law and Ethics for Pharmacy Technicians, now in its Third Edition, is designed specifically to provide technicians with the legal and ethical information they need to perform their jobs with absolute confidence. It covers all U.S. federal laws regarding pharmacy practice as well as other laws and regulations and their applicability to pharmacy technicians. It also addresses current issues such as herbal medications, privacy laws and rules, and drug pedigree. A unique section on ethics offers extensive discussion points and cases. Appendices provide extensive information on practice regulation in all states.Fully revised to address the latest procedural, ethical, and technological developments in this rapidly changing field, this third edition of a bestseller has been edited for clarity and provides a wealth of new material, including a new appendix on the legal status of electronic transmission of prescriptions. It covers the latest in state and federal regulations pertaining to the administration of new medications, including birth control and the morning-after pill, as well as new regulations on over-the-counter label claims.An essential resource for students and practicing technicians, this reference brings together the information that pharmacy technicians need to practice in a manner that is both legal and ethical. What's New in this Edition: Updated information on over-the-counter label claims Updated sections on drug samples and the Combat Methamphetamine Epidemic Act of 2005 New sections on drug pedigrees and United States Pharmacopoeia Chapter